Molecular epidemiology of hepatitis C in Kelantan - Amin, Nur Amalin Zahirah Mohd (2024)
Hepatitis C is a major public health threat that affects millions of individuals globally. Chronic Hepatitis C is one of the primary causes of chronic liver disease worldwide, which can develop to liver cirrhosis and hepatocellular cancer if not treated efficiently. The persistent finding of novel Hepatitis C virus (HCV) genotypes and subtypes is the proof of the virus's continued genetic development. The HCV genotype that causes the infection is critical for effective medication and management. Therefore, adequate HCV screening and quantification are critical for the diagnosis and proper management of the disease. Thus, this study aims to determine the prevalence of HCV genotypes and risk factors associated with HCV infection in Kelantan as well as to establish an in-house nested reverse-transcriptase polymerase chain reaction (RT-PCR) assay for HCV detection in Kelantan. This cross-sectional study was conducted at Microbiology Laboratory with the participation of patients recruited from Hospital Universiti Sains Malaysia and Hospital Raja Perempuan Zainab 2 from December 2019 until January 2022. The result of this study showed that 56 out of 80 patients were detected HCV positive by nested RT-PCR. A total of three genotypes were found with the most frequent genotype were HCV genotype 3 and 1 with a similar proportion of 44.6% (25) each and 1.8% (1) from genotype 6. For genotype 3, two subtypes were found with 41% (23) of subtype 3a, followed by 3.6% (2) of subtype 3b. For genotype 1, most subtypes were from subtype 1a, 42.9% (24) and only 1.8% (1) from subtype 1b was observed. The only participant with genotype 6 was found to be subtype 6n, 1.8% (1). However, there were five (8.9%) mixed genotypes discovered in this study which were: 3a/1a (5.4%) (3), 3b/1a (1.8%) (1), 1a/3a (1.8%) (1). From this study, there was a significant association in occupation according to gender of HCV patients. However, no association found in age and marital status based on gender. There was also significant association between male patients with risk factors of intravenous drug user (IVDU) and blood transfusion. However, no association found between the genotypes with the risk factors of HCV transmission. In conclusion, both of genotypes 3 and 1 were the most common HCV genotypes found in this study population. Furthermore, the highest risk factors of HCV transmission were IVDUs and blood transfusion. In sum, these findings may guide future epidemiological studies on HCV prevalence and transmission in Kelantan.